Revised safety evaluation of the food enzyme endo‐1,3(4)‐β‐glucanase from the non‐genetically modified Cellulosimicrobium funkei strain AE‐TN - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme endo‐1,3(4)‐β‐glucanase (3‐(1–3;1–4)‐β‐D‐glucan 3(4)‐glucano‑hydrolase; EC 3.2.1.6) is produced with the non‐genetically modified (GM) Cellulosimicrobium funkei strain AE‐TN by Amano Enzyme Inc. The production organism belongs to a species implicated in opportunistic infections in humans. In a previous evaluation, the Panel did not consider the food enzyme safe due to the presence of viable cells of the production strain in the food enzyme. As a follow‐up, the applicant improved the quality assurance system by introducing a pressure check of the microfiltration step of the food enzyme manufacturing process and the production strain was no longer detected in new food enzyme batches. The Panel accepted the results. Based on the new data and the previous evaluation, the Panel concluded that the food enzyme endo‐1,3(4)‐β‐glucanase produced with the non‐GM C. funkei strain AE‐TN does not give rise to safety concerns under the intended conditions of use.